Hyperlipidemia in APOE2 transgenic mice is ameliorated by a truncated apoE variant lacking the C-terminal domain - Gery Gerritsen; Kyriakos E. Kypreos; André van der Zee; Bas Teusink; Vassilis I. Zannis; Louis M. Havekes; Ko Willems van Dijk (Journal of Lipid Research, 2003)
Familial dysbetalipoproteinemia associated with the apolipoprotein E2 (APOE2) genotype is a recessive disorder with low penetrance. We have investigated whether additional expression of full-length APOE3, APOE4, or a truncated variant of APOE4 (APOE4-202) can reduce APOE2- associated hyperlipidemia. This was achieved using adenovirus-mediated gene transfer to mice transgenic for human APOE2 and deficient for endogenous Apoe (APOE2.Apoe−/− mice). The hyperlipidemia of APOE2.Apoe−/− mice was readily aggravated by APOE3 and APOE4 overexpression. Only a very low dose of APOE4 adenovirus was capable of reducing the serum cholesterol and triglyceride (TG) levels. Expression of higher doses of APOE4 was associated with an increased VLDL-TG production rate and the accumulation of TG-rich VLDL in the circulation. In contrast, a high dose of adenovirus carrying APOE4-202 reduced both the cholesterol and TG levels in APOE2.Apoe−/− mice. Despite the absence of the C-terminal lipid-binding domain, APOE4-202 is apparently capable of binding to lipoproteins and mediating hepatic uptake. Moreover, overexpression of APOE4-202 in APOE2.Apoe−/− mice does not aggravate their hypertriglyceridemia. These results extend our previous analyses of APOE4-202 expression in Apoe−/− mice and demonstrate that apoE4-202 functions even in the presence of clearance-defective apoE2.Thus, apoE4-202 is a safe and efficient candidate for future therapeutic applications.